Review of critical thinking and fighting spirit among athletes. - Sulaiman, Tajularipin; Baki, Roselan; Abdullah, Borhannudin; Garmjani, Maryam Gholampour; Motevalli, Saeid (Center for Promoting Ideas (CPI), USA, 2013)
This paper is written as a conceptual paper where the main purpose is to discuss about the importance of critical thinking and fighting spirit on athlete’s performance. Cognitive approach as one of the famous approaches in psychology concentrates on the important role of mental processes such as processing and remembering new information, developing language, problem solving, and thinking. Moreover, critical thinking specifically emphasises on some cognitive processes which attempt to minimize the influence of preconceptions and biases while rationally assessing evidence and signs, concluding on the base of interpretation of evidences and signs, and concerning alternative explanations. On the other hand, fighting spirit refers to the internal motivation due to enhance the athletes’ performance through the sport competition. The authors explain the definitions of cognitive approach, critical thinking, fighting spirit as internal motivation among athletes, and also a briefly discussion on importance of critical thinking skills among athletes are included in the discussion. Future direction in critical thinking research and fighting spirit among athletes is brought up as well suggestion to psychologists and sport psychologist to embark critical thinking research.